Das Ritual der Aštu (CTH 490) : Rekonstruktion und Tradition eines hurritisch-hethitischen Rituals aus Boğazköy/Ḫattuša - Görke, Susanne. (Culture and History of the Ancient Near East, 2010)
The Ritual of Aštu, a text found at the Hittite Capital of Hattuša, shows strong influence from southern Anatolia and describes a Hurrian-Hittite ritual against witchcraft and sorcery. The following study provides detailed philological treatment of the 13th-century fragments found at Hattuša, from which the ritual is known, including transcription, translation, and commentary of all manuscripts, as well as special emphasis on the Hurrian passages of the ritual. Reconstruction of the more fragmentary sections is undertaken through comparison to other rituals. The study concludes with an analysis of Anatolian, Luwian, and Kizzuwatnaian influences evident in the ritual, and affords, in sum, valuable additions to the study of the nature of Hittite archives, and the development of ritual texts. "I firmly believe that works like this are essential to creating the dialogue that is necessary for the progress of our understanding of Hurrian. Görke's treatment of the various texts and her discussions of many aspects of the ritual will prove very useful to scholars working on Hurro-Hittite religion." Dennis R.M. Campbell, San Francisco State University